Clinicians' Views of Patient-initiated Follow-up in Head and Neck Cancer: a Qualitative Study to Inform the PETNECK2 Trial. Issue 4 (April 2022) - Lorenc, A.; Wells, M.; Fulton-Lieuw, T.; Nankivell, P.; Mehanna, H.; Jepson, M.; ,; Karwath, A.; Main, B.; Firth, C.; Gaunt, C.; Greaves, C.; et al.
Abstract: Aims: Current follow-up for head and neck cancer (HNC) is ineffective, expensive and fails to address patients' needs. The PETNECK2 trial will compare a new model of patient-initiated follow-up (PIFU) with routine scheduled follow-up. This article reports UK clinicians' views about HNC follow-up and PIFU, to inform the trial design. Materials and methods: Online focus groups with surgeons (ear, nose and throat/maxillofacial), oncologists, clinical nurse specialists and allied health professionals. Clinicians were recruited from professional bodies, mailing lists and personal contacts. Focus groups explored views on current follow-up and acceptability of the proposed PIFU intervention and randomised controlled trial design (presented by the study co-chief investigator), preferences, margins of equipoise, potential organisational barriers and thoughts about the content and format of PIFU. Data were interpreted using inductive thematic analysis. Results: Eight focus groups with 34 clinicians were conducted. Clinicians highlighted already known limitations with HNC follow-up – lack of flexibility to address the wide-ranging needs of HNC patients, expense and lack of evidence – and agreed that follow-up needs to change. They were enthusiastic about the PETNECK2 trial to develop and evaluate PIFU but had concerns that PIFU may not suit disengaged patients and may aggravate patient anxiety/fear of recurrence and delay detection of recurrence. Anticipated issues with implementation included ensuring a reliable route back to clinic and workload burden on nurses and allied health professionals. Conclusions: Clinicians supported the evaluation of PIFU but voiced concerns about barriers to help-seeking. An emphasis on patient engagement, psychosocial issues, symptom reporting and reliable, quick routes back to clinic will be important. Certain patient groups may be less suited to PIFU, which will be evaluated in the trial. Early, meaningful, ongoing engagement with clinical teams and managers around the trial rationale and recruitment process will be important to discourage selective recruitment and address risk-averse behaviour and potential workload burden. Highlights: Head and neck cancer clinicians agree follow-up regimens need to change. If proven effective, patient-initiated follow-up may improve patient-centredness. Clinician concerns include the suitability of patient-initiated follow-up for all. Patient-initiated follow-up may impose additional burden on some clinicians. Patient-initiated follow-up may not suit 'disengaged'/high-risk/deprived patients.